Current concepts related to the prescription of antibacterials in Dentistry: literature review (Research, Society and Development, 2020)
In dentistry, antibacterial drugs are indicated for pre-established infections, as well as for the prevention of bacteremia in the face of invasive procedures in patients with a systemic condition that allows the spread of these bacteria in the bloodstream. Therefore, the objective of the present study was to review in the scientific literature, the current concepts related to the prescription of antibacterials in dentistry. It is of utmost importance to create measures to correctly carry out the antibacterial prescription, in order to avoid an inappropriate prescription of these drugs. The improper use of these drugs causes damage to the patient's systemic health, contributing to bacterial resistance. The rational use of these drugs also encompasses the health professional's knowledge about the prescribed substance, and the user must correctly guide the user regarding the dosage and the intervals for using the drug. The training of the dental surgeon on the theoretical and practical knowledge of pharmacology must be constantly updated, since the prescription encompasses everything from the use of substances to the necessary information that must be contained.